"Amar beton khub e kom": The Role of Commercial Recruitment Intermediaries in Reinforcing Gendered and Racialised Inequalities. (14th June 2022) - Shah, Heila; Bhuiyan, Mohammad Rashed Alam
Abstract : The 2030 Agenda on Sustainable Development explicitly links the goal of reducing inequality between and within countries to the encouragement of orderly, safe, regular and responsible migration. Yet to date there has been little discussion on how migration processes, especially those which occur through commercialised recruitment intermediaries may, in fact, enhance rather than reduce socio-economic inequalities. In particular, existing research shows that migrant workers from the Global South, especially in Asia, are often recruited by intermediaries into low paid, temporary and precarious jobs such as domestic service and hospitality work, agriculture and construction, manufacturing and mining. Such workers are often recruited as cheap, flexible labour and denied access to the right to organise in trade unions. Moreover, intermediaries often charge migrants fees for recruitment which inhibit their ability to maximise their earnings and remit monies home. This article addresses one of the hitherto neglected yet most fundamental aspects of international migration: how commercialised recruitment intermediaries serve to reinforce racialised and gendered inequalities. The article draws on a content analysis of recent articles published in the media on Bangladeshi migrant workers, aiming to contribute to discussions of gender, race and inequality in international migration and domestic labour through the lens of intersectional analysis.